A protocol to measure the impact of intentional changes to nurse staffing and skill‐mix in medical and surgical wards. (29th August 2018) - Drennan, Jonathan; Duffield, Christine; Scott, Anne Philomena; Ball, Jane; Brady, Noeleen M.; Murphy, Aileen; Dahly, Darren; Savage, Eileen; Corcoran, Paul; Hegarty, Josephine; Griffiths, Peter
Abstract: Aim: The aim of this research is to measure the impact that planned changes to nurse staffing and skill‐mix have on patient, nurse, and organizational outcomes. Background: It has been highlighted that there are several design limitations in studies that explore the relationship between nurse staffing and patient, nurse and organizational outcomes; not least that the vast majority of research in this area emanates from studies that are predominantly observational in design. There are limited studies that measure nurse, patient, organizational, and economic outcomes using a longitudinal design following a planned change in nurse staffing. Design: The research will employ a longitudinal, multimethod approach to evaluate the impact that planned changes in nurse staffing and skill‐mix have on wards in three pilot hospitals. Methods: Administrative data collection will take place on a shift‐by‐shift basis prospectively over a three‐year period including the measurement of nursing sensitive outcomes: cross‐sectional patient experience data and nurse outcomes (nursing work, job satisfaction, burnout, missed care) will be collected at intervals prior to, during and after the implementation of planned changes in nurse staffing and skill‐mix. Data will be analysed using interrupted time‐series models, adjusted for key hospital, ward and patient‐level factors. An economic costing of the changes will further investigate the resources required for the intervention that can then be aggregated to a national level for future roll‐out plans. Discussion: The study aims to provide evidence on the impact of planned changes to nurse staffing and skill‐mix based on a systematic approach using a longitudinal design and to determine the extent to which the approach can be implemented at a national level.